The Effectiveness of group counseling based on problem-solving on experiencing domestic violence among pregnant women: A clinical trial - Masoumeh Alamshahi; Forouzan Olfati; Saeed Shahsavari; Maryam Taherpour (Wolters Kluwer Medknow Publications, 2020)
Introduction: Domestic violence is highly prevalent during pregnancy and affects both the mother and fetus. Problem-solving training showed to be useful in controlling different crises of life including anger and aggression. Thus, the present study aimed to investigate the effectiveness of group counseling based on problem-solving on experiencing domestic violence among pregnant women. Methods: This study is a clinical trial which was conducted on eighty pregnant women referred to Buin Zahra urban centers in 2019. The individuals were randomly divided into intervention (n = 40) and control (n = 40) groups. Six 45-min sessions for five groups of eight people were implemented for the intervention group. The violence was examined before, immediately, and 3 months after the intervention using the Revised Conflict Tactics Scale instrument. Sociodemographics and obstetrics characteristics were compared using Chi-square. Data were analyzed using repeated-measures analysis of variance at a significance level of < 0.05. Results: The baseline characteristics were homogeneous between the two groups. After intervention, the mean score of violence decreased statistically significantly for the intervention group versus control group immediately after (159.28 vs. 190.98, P < 0.001) and 3 months after the intervention (117.85 vs. 198.9, P < 0.001). Conclusion: Group counseling based on problem-solving is effective on the level of domestic violence among pregnant women. Therefore, using this method of counseling during pregnancy can be associated with positive results in reducing domestic violence.